Assessing The Implications and Future Perception of Biological Disaster a Covid 19 Pandemic on The Wellbeing of The Residents of Ekiti State - Oluwayemisi, Ogunleye (Amcolabora, 2023)
This research was done in order to assess the implication of covid-19 pandemic, a biological disaster, on the wellbeing of the Residents of Ekiti State and it is also to discover future perception of the residents towards biological disaster Preparedness and awareness. Well designed, open ended questionnaires were administered randomly to some residence of Ekiti State during the covid – 19 pandemic and lock down. The collected data were analyzed using simple frequency counts, percentages and chi-square. The negative impacts of covid – 19 according to findings were the loss of means of livelihood, restriction of movement, enforcement of the use of nose mask even when it was not convenient or appealing to the body, increased hunger and anxiety while the positive impacts included: better and cordial relationship among couples and families, compulsory and sufficient rest which improved the health conditions of the people. All impacts occurred unprepared for, consequently, biological disaster preparedness and management should be of paramount importance and concern to everyone and should be a national and community priority as part of the coping strategies in times future occurrence